(untitled) (Research, Society and Development, 2021)
Syphilis is a sexually transmitted infection caused by Treponema Pallidum, where treatment during pregnancy is indispensable, but if left untreated it can progress to early neonates and fetal death. A congenital infection is a condition of compulsory notification, categorized as infectious disease due to the spread of T. pallidum transplacentally during pregnancy. In Brazil, data from the Ministry of Health bulletin 2018 were reported 158,051 case cases where 26,219 cases represent cases of evolutionary conflict for 241 cases. This article aimed to describe the profile of pregnancy cases, reported in the Northeast region, Brazil, from 2009 to 2018. An epidemiological survey of congenital individuals in the Northeast region from 2009 to 2018 was performed. Survey demonstrated increase in diagnosis per year every thousand live births, as observed in pregnant women aged 20 to 29 years, as well as in the diagnosis during the second and third trimester of pregnancy, in addition to showing an increasing number in cases of adherence to treatment, portraying the increasing number of mothers who had or pre-performed -Christmas. The prevalence of syphilis was observed in women with lower education level. As a result of the data collection, you can see the relevance of the study presented, considering the epidemiological importance of these data for the application of public policies.